“Perversion to match the curtains”? Grayson Perry’s tranny aesthetic - Margaret GILLESPIE (E-REA)
Grayson Perry CBE, winner of the 2003 Turner Prize, is one of Britain’s most prominent contemporary multi-media artists and cultural commentators. Married to Philippa and a father to daughter Flo, Perry is also an “out” practising cross-dresser, famed for his female alter ego Claire. This article attempts to assess the role of transvestism in Perry’s work and gauge its provocative potential in the light of the artist’s own increasingly established position within the cultural mainstream. Concentrating particularly on his ceramic art and the artist’s public appearances in drag, it will be argued that cross-dressing remains central to Perry’s aesthetic and that the blurring of gender binaries offers one of the keys to understanding Perry’s ambiguous and incongruous status as at once deeply subversive and yet conventional and homely: “perversion to match the curtains” in his own words.